A cat from our world and the forgotten witch. Vol. 4 - Kashiwaba, Hiro; Kindya, Kimberly (Seven Seas Entertainment, 2025)
"Rue's hidden magical power is blazing out of control, so Robbins brings her back to the royal palace for treatment. Jeanne senses that the girl is in danger and leaves her forest home for the first time in fifty years, bringing her giant cat Mew and the mercenary, Flad. Waiting for her in the palace is her old nemesis the Dowager Empress--and a Guardian Beast who once stood by Jeanne's side!"--